Pharmacotherapy as major risk factor of falls – analysis of 12 months experience in hospitals in South Bohemia - Malý, Josef; Doseděl, Martin; Vosátka, Jan; Malá-Ládová, Kateřina; Kuběna, Aleš Antonín; Brabcová, Iva; Hajduchová, Hana; Bártlová, Sylva; Tóthová, Valérie; Vlček, Jiří (Jihočeská univerzita v Českých Budějovicích, Zdravotně sociální fakulta, 2019)
This study aimed to analyze the effect of fall risk-increasing drugs (FRIDs) and drug-related factors relative to falls through clinical pharmacy service in hospitalized patients, focusing on the relevance of clinical pharmacist evaluation in the context of physician assessment. A prospective study of inpatient falls was conducted in 2017 retrieving data from 4 hospitals in South Bohemia, Czech Republic. An online database was developed to collect patient and fall-related data, and fall evaluation records. Healthcare professionals classified the overall effect of drugs on falls using Likert scale. Univariate and multivariate correlations were performed with a significance level of p < 0.05. Out of the total 280 falls (mean age of patients 77.0 years), a mean of 2.8 diagnoses with fall-related risk, 8.8 drugs, and 4.1 FRIDs per fall were identified. Incidence of falls decreased quarterly (p < 0.001). Use of FRIDs were positively associated with increasing age (p = 0.007). Clinical pharmacists were more likely to identify pharmacotherapy as the relevant fall-related risk, compared to physicians evaluation (p < 0.001). An increasing total number of prescribed drugs as well as higher number of FRIDs increased the suspicion in both professionals in the context of drug-related causes of falls.
Keywords: Clinical pharmacy service; Drug therapy; Fall risk-increasing drugs; Falls; Hospital inpatients